Temporal variation of the algae-associated molluscan assemblage of artificial substrata in Bay of Tunis (Tunisia) - ANTIT, M.; DAOULATLI, A.; RUEDA, J.L.; SALAS, C. (Mediterranean Marine Science, 2013)
The molluscan assemblage inhabiting the photophilous algae from artificial rocky shores in theBay of Tunis) was studied from February 2009 to February 2010. Five monthly replicates were taken with a quadrat of 25 × 25 cm .. A total of 16105 individuals of molluscs, belonging to 93 species, were collected. Gastropods were the most species-rich group, with 66 species (70.96%), followed by bivalves with 26 species (27.95%). Gastropods were also the most abundant with 11529 individuals (71.60%), followed by bivalves with 4575 individuals (28.41%). Nevertheless,Mytilaster minimus was the dominant species overall during the studied period (15.6% of total abundance), followed by Tricolia miniata (11.6%), Bittium reticulatum (11.5%), Gibbula racketti (10.4%) and Rissoa similis (9.8%). The high abundance of juveniles of soft (e.g. Venerupis aurea, Nassarius corniculum) and hard bottom species (e.g. M. minimus, Fissurella nubecula) point out the important role of this habitat as nursery for species from nearby located habitats. The presence of the alien molluscs Mitrella psilla (2.5% dominance) and Arcuatula senhousia highlights the importance of algae as vehicle and/or receptor habitat for alien species. Species richness and abundance displayed significant seasonal changes, with maxima in winter 2009, but the Shannon-Wiener diversity index showed similar values throughout the year. Multivariate analyses also indicated the presence of significant seasonal differences of this molluscan assemblage.